Stream sediments pollution: A compositional baseline assessment at the Caveira mine, Portugal - Araújo, Joana (2022)
A high concentration of Potentially Toxic Elements (PTE) can affect ecosystem health. It is therefore essential that spatial trends of pollutants are assessed and controlled. River sediment pollution is widespread in mining communities around the world, including in developing countries. This study, as part of the GeoMaTre project, restoration of water bodies impacted by mine drainage, an ongoing collaborative project (2021-2024) between the Polytechnic Institute of Castelo Branco and the University of Évora, Portugal, aimed to evaluate the potential risk of PTEs pollution in stream sediments under the direct influence of Caveira mine, a Cu-Pb Zn-Ag-Au old mine included in the Iberian Pyrite Belt, South Portugal. Quantifying pollution implies first the understanding of pollution-free stream sediment. Often, this background, or pollution baseline, is undefined or only partially known. Given that the concentration of chemical elements is compositional, as the attributes vary together, a compositional approach was used aiming to find a compositional balance, based on Compositional Data (CoDa) principles. A dataset of 33 samples was collected from within 0 to 10 cm depth, in a grid of 1Km x 1Km and thirteen chemical elements, including PTEs of variable toxicity (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Zn, V) and major elements from lithogenic sources (Fe, Al), were analyzed in preservedsamples at about 4°C. The most extractable forms of metals (except for Hg) were obtained by partial digestion with aqua regia (HCl and HNO3) in a high-pressure microwave digestion unit, followed by ICP-OES analysis. Hg was analyzed determined by a mercury analyzer based on thermal decomposition, gold amalgamation, and cold vapor atomic absorption spectroscopy detection.